Impacts of Land Use on Indian Mangrove Forest Carbon Stocks: Implications for Conservation and Management - Bhomia, R.K.; Mackenzie, R.A.; Murdiyarso, Daniel; Sasmito, S.D.; Purbopuspito, J. (Wiley, 2016)
Globally, mangrove forests represents only 0.7% of world's tropical forested area but are highly threatened due to susceptibility to climate change, sea level rise, and increasing pressures from human population growth in coastal regions. Our study was carried out in the Bhitarkanika Conservation Area (BCA), the second‐largest mangrove area in eastern India. We assessed total ecosystem carbon (C) stocks at four land use types representing varying degree of disturbances. Ranked in order of increasing impacts, these sites included dense mangrove forests, scrub mangroves, restored/planted mangroves, and abandoned aquaculture ponds. These impacts include both natural and/or anthropogenic disturbances causing stress, degradation, and destruction of mangroves. Mean vegetation C stocks (including both above‐ and belowground pools; mean ± standard error) in aquaculture, planted, scrub, and dense mangroves were 0, 7 ± 4, 65 ± 11 and 100 ± 11 Mg C/ha, respectively. Average soil C pools for aquaculture, planted, scrub, and dense mangroves were 61 ± 8, 92 ± 20, 177 ± 14, and 134 ± 17 Mg C/ha, respectively. Mangrove soils constituted largest fraction of total ecosystem C stocks at all sampled sites (aquaculture [100%], planted [90%], scrub [72%], and dense mangrove [57%]). Within BCA, the four studied land use types covered an area of ~167 km2 and the total ecosystem C stocks were 0.07 Tg C for aquaculture (~12 km2), 0.25 Tg C for planted/ restored mangrove (~24 km2), 2.29 teragrams (Tg) Tg C for scrub (~93 km2), and 0.89 Tg C for dense mangroves (~38 km2). Although BCA is protected under Indian wildlife protection and conservation laws, ~150 000 people inhabit this area and are directly or indirectly dependent on mangrove resources for sustenance. Estimates of C stocks of Bhitarkanika mangroves and recognition of their role as a C repository could provide an additional reason to support conservation and restoration of Bhitarkanika mangroves. Harvesting or destructive exploitation of mangroves by local communities for economic gains can potentially be minimized by enabling these communities to avail themselves of carbon offset/conservation payments under approved climate change mitigation strategies and actions.